A Simple and Sensitive RT-qPCR Technology for Rapid Detection of Porcine Reproductive and Respiratory Syndrome Virus - Hongri Zhao; Xingyu Xiao; Yajuan Sun; Yang Chen; Yongzhe Zhang; Peng Li; Hui Jin; Ying Li; Rui Yin (Veterinary Sciences)
To establish a rapid and sensitive detection method for the porcine reproductive and respiratory syndrome virus (PRRSV), gene-specific primers and a TaqMan probe were designed based on the M gene of PRRSV, and a new stable fully pre-mixed reverse transcription real-time fluorescence quantitative PCR (RT-qPCR) reaction mixture was developed. A simple and rapid RT-qPCR detection method for PRRSV was developed by optimizing nucleic acid amplification conditions. The results showed that the method was able to specifically detect PRRSV without cross-reactivity with the other 11 porcine susceptible viruses. The sensitivities of the assay were 3.12 × 100 copies/μL and 100 TCID50/μL for M gene and virus, respectively, and the repeatability and reproducibility (relative standard deviation, CV) of the assay were less than 2.5%. Based on the new fullly pre-mixed RT-qPCR reaction mixture, the RT-qPCR detection method may provide a new, simple, and rapid method for accurately detecting PRRSV.